PENERAPAN KETERAMPILAN MEMBATIK IKAT UNTUK MENINGKATKAN KEMAMPUAN MOTORIK HALUS ANAK TUNAGRAHITA RINGAN KELAS KECIL DI SLB - FITRI A P, RIANA (Jurnal Pendidikan Khusus, 2017)
ABSTRACT This research is motivated by fine motor as the main obstacle, so it need to be given a fun learning through batik making activity, which has never been done before. The purpose of this study is to test the improvement of fine motor abilities of children with mild intelectual disability by applying batik skill. The research method used in this research is quantitative approach of pre experimental design with one group pre test - post test design. Statistical techniques in the analysis of this research data is the sign test or Sign Test. Technique of collecting data in the form of test, observation and documentation. The subjects used were six students with mild intelectual disability. The results showed that the value of Z arithmetic (Zh) = 2.04 is greater than the value of crisis Z table (Zt) 5% = 1.96 (Zh> Zt), then Ho is rejected Ha accepted, so there is an increase in fine motor skills Children with mild intelectual disability apply the skills of batik.   Keywords: Batik Skills, Fine Motor.